2011
DOI: 10.19030/tlc.v6i5.1144
|View full text |Cite
|
Sign up to set email alerts
|

Using Translated Instruments In Research

Abstract: International and cross cultural research in the global community often requires translations of instruments. This paper reviews the development of a translation protocol for instruments written in English for a Western culture and used for a different language and culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…Over 122 major languages have been identified in India. 7 Developing new language specific questionnaires is demanding in terms of time, money and effort 8 and hence, translation of questionnaires to local languages and cultures would be a more practical method. The goal of the present study was to translate and adapt five commonly used self-report English health questionnaires into a South Indian language, Kannada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 122 major languages have been identified in India. 7 Developing new language specific questionnaires is demanding in terms of time, money and effort 8 and hence, translation of questionnaires to local languages and cultures would be a more practical method. The goal of the present study was to translate and adapt five commonly used self-report English health questionnaires into a South Indian language, Kannada.…”
Section: Introductionmentioning
confidence: 99%
“…Using a team of translators with supplementary skills like good familiarity with local culture, in-depth knowledge of the field, and expertise with the research methodology and translation process is recommended too. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Cross-cultural adaptation of scales with proper processes enable researchers to carry out multicultural studies and contribute to international collaboration (Çapık, Gözüm & Aksayan, 2018). Cultural adaptation also saves time, money and effort (Beauford, Nagashima & Wu, 2009). Accordingly, it can be observed that scale adaptation studies are increasing nowadays (Açak & Düz, 2018;Altundağ, Yandı & Ünal, 2019;Dilekçi & Sezgin Nartgün, 2020;Limon & Durnalı, 2017;Yılmaz, 2019 e.g.).…”
Section: Methods Research Modelmentioning
confidence: 99%
“…In the literature, various steps are suggested for scale adaptation (Beauford, Nagashima, & Wu, 2009;Dhamani & Richter, 2011;Gjersing, Caplehorn & Clausen, 2010). However, this study employed the steps suggested by Gjersing et al (2010).…”
Section: Language Adaptation Processmentioning
confidence: 99%
“…В соответствии с классическими психометрическими стандартами (Beauford et al, 2009) перевод русскоязычной краткой версии ДТП на английский язык осуществлялся с помощью процедуры обратного перевода при участии трех специалистов, в совершенстве владеющих русским и английским языками. При переводе на английский язык методика получила название Brief Differential Perfectionism Inventory (BDPI), а ее шкалы -«Normal perfectionism» (NP) и «Pathological per-fectionism» (PP).…”
Section: исследованиеunclassified